2020
DOI: 10.3390/toxics8020045
|View full text |Cite
|
Sign up to set email alerts
|

Combining Different In Vitro Bioassays to Evaluate Genotoxicity of Water-Accommodated Fractions from Petroleum Products

Abstract: Genotoxicity assessment is of high relevance for crude and refined petroleum products, since oil compounds are known to cause DNA damage with severe consequences for aquatic biota as demonstrated in long-term monitoring studies. This study aimed at the optimization and evaluation of small-scale higher-throughput assays (Ames fluctuation, micronucleus, Nrf2-CALUX®) covering different mechanistic endpoints as first screening tools for genotoxicity assessment of oils. Cells were exposed to native and chemically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…Though a comparison using induction factors accounts for inter-species variability [21], a direct comparison of different oil exposure studies is limited due to a variety of selected exposure conditions and oil types. Nonetheless, in a previous study using the identical NNS crude oil batch we also found stronger micronucleus formation in acutely exposed (48 h) permanent zebrafish liver cells [61]. The higher sensitivity of the cell line compared to erythrocytes demonstrates the lack of toxicokinetics in in vitro bioassays and highlights the in situ micronucleus assay as a relevant endpoint for a more reliable ecotoxicological risk assessment of oil WAFs.…”
Section: Genotoxicitysupporting
confidence: 47%
See 1 more Smart Citation
“…Though a comparison using induction factors accounts for inter-species variability [21], a direct comparison of different oil exposure studies is limited due to a variety of selected exposure conditions and oil types. Nonetheless, in a previous study using the identical NNS crude oil batch we also found stronger micronucleus formation in acutely exposed (48 h) permanent zebrafish liver cells [61]. The higher sensitivity of the cell line compared to erythrocytes demonstrates the lack of toxicokinetics in in vitro bioassays and highlights the in situ micronucleus assay as a relevant endpoint for a more reliable ecotoxicological risk assessment of oil WAFs.…”
Section: Genotoxicitysupporting
confidence: 47%
“…It is important to mention that an additional control group with the dispersant alone was not included within the current study to experimentally address the role of the dispersant. From our previous studies with the dispersant Finasol OSR 51, which shows high comparability to Finasol OSR 52 used in the present study, we have to emphasize that the toxicity of the dispersant alone or in combination with an inert oil cannot be excluded per se [61][62][63]). Nonetheless, the dispersant-induced general toxicity (oxidative stress induction) or acute toxicity to zebrafish embryos and larvae were found in exposure concentrations highly elevated compared to the exposure concentrations used in the present study.…”
Section: Critical Considerations For Dispersant Toxicity Interpretation In Chronic Exposure Studiesmentioning
confidence: 72%
“…HTS methods are defined as the use of automated tools to facilitate rapid execution of a large number and variety of biological assays that may include several test substances in each assay [ 162 ]. 134 publications have been found applying the keywords “genotoxicity & high throughput“ [ 163 , 164 , 165 , 166 , 167 , 168 ], although only 14 of them related to NMs ( Table 1 ).…”
Section: High Throughput Methodsmentioning
confidence: 99%
“…Additionally, single-cell strategies cannot differentiate damage from xenobiotic agents that are not available due to their association with organic matter. The toolbox for assessing genotoxicity in different samples is ample (Johann et al 2020 ), such as cell viability by MTT assays (Mosmann 1983 ), oxidative stressors by Nrf2-CALUX (Steinberg et al 2016 ), micronucleus assay for chromosomal aberrations (ISO 21427-2) and the Ames mutagenicity assay (ISO 11,350).…”
Section: Discussionmentioning
confidence: 99%